2021
DOI: 10.3390/foods10102317
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock Affects the Fruit Quality of ‘Early Bigi’ Sweet Cherries

Abstract: The cherry rootstock influences the performance of the scion cultivar. It has an effect on cherry fruit quality, tree growth, yield and yield efficiency and floral and foliar nutrition. In this work, the influence of Saint Lucie 64 and Maxma 60 rootstocks on the fruit quality traits of cv. Early Bigi was evaluated. For this, several parameters, namely fruit weight (FW) and size (FS), soluble solids content (SSC), pH, titratable acidity (TA), flesh firmness (FF), epidermis rupture force (ERF), color and sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 63 publications
(80 reference statements)
1
2
0
Order By: Relevance
“…The compatibility treatment did not present significant differences in the fruit's respiratory variables, growth, and development. This result is suchlike that reported in other fruit species, where Martins et al (2021) found in cherry (Prunus avium L.) that the compatibility between the rootstock and the graft does not affect the quality of the fruit, having a similar diameter, length, and weight in plants evaluated with these morphological differences. Fredes et al (2016) assessed the effect of the rootstock in the cultivation of watermelon (Citrullus lanatus), and no significant differences were found in the growth and development of the fruits compared to incompatible graft treatments.…”
Section: Fruit Growth and Development -Harvest Season (H) As The Main...supporting
confidence: 87%
“…The compatibility treatment did not present significant differences in the fruit's respiratory variables, growth, and development. This result is suchlike that reported in other fruit species, where Martins et al (2021) found in cherry (Prunus avium L.) that the compatibility between the rootstock and the graft does not affect the quality of the fruit, having a similar diameter, length, and weight in plants evaluated with these morphological differences. Fredes et al (2016) assessed the effect of the rootstock in the cultivation of watermelon (Citrullus lanatus), and no significant differences were found in the growth and development of the fruits compared to incompatible graft treatments.…”
Section: Fruit Growth and Development -Harvest Season (H) As The Main...supporting
confidence: 87%
“…Identification concerning the hydroxycinnamic acid profile is in accordance with previous research, which identifies caffeoylquinic acid derivatives, caffeic acid derivatives, and coumaroylquinic acid derivatives as the major hydroxycinnamic components in cherries [ 40 ]. According to the previous results, the content of enumerated components of hydroxycinnamic acids varies greatly depending on the cultivar and rootstock [ 23 , 25 , 41 ]. The dominance of caffeoylquinic acid derivatives in all the samples was the same as in the plum cultivar ‘Čačanska lepotica’ grafted onto five different rootstocks [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grafting can be used to avoid juvenility of perennial woody species and can confer important agronomic traits to scions such as uniformity of plant architecture and tolerance to biotic and abiotic stresses [1][2][3][4]. In addition, the scion-rootstock combination can influence tree vigor, yield and fruit quality, and can extend the harvest season [5,6]. Following the advent of in vitro plant tissue culturing in the early 1900s [7], a grafting system using tissue culture (micrografting) was first demonstrated by Doorenbos [8] in ivy and then Holmes [9] in chrysanthemum in the 1950s, and was later developed and standardized for virus eradication from citrus species by Murashige et al [10] and Navarro et al [11].…”
Section: Overall Developments and Characters Of Micrograftingmentioning
confidence: 99%